Análise crítica de pornografias feministas: diálogos com os feminismos e ressignificações da sexualidade - Fernandes, Liliana Rocha (2022)
Pornography and Feminism were in opposition for a long time, and, even today, this relationship ignites heated debates. Anti-pornography feminism has its roots in the theoretical discussion held especially in the United States of America in the 1970s and 1980s, called the Feminist Sex Wars. Broadly speaking, this movement advocated the censorship of pornographic materials, on the grounds that pornography promoted violence against women. Pro-sex feminists, on the other hand, fought for sexual emancipation, along with all the oppression experienced by women in relation to their sexuality. The present research analyzes the pornographic production called feminist, contextualizing it with the aforementioned debate, based on the feminist theoretical framework and authors of porn studies. One of the main points defended by the directors who propose to produce feminist and dissident pornography is to break with the sexist discourses that prevail in mainstream pornography, producing new ways of demonstrating sex, from a perspective that also privileges female pleasure. Considering this assumption, three specific films are analyzed: Gender Bender (2018, Erika Lust), Skin (2009, Elin Magnusson) and Landlocked (2018, Lívia Cheibub). Using narrative conventions of traditional pornography as categories of comparative analysis of sexual performances, we seek to identify the resignifications or de-territorializations of discourses on sexuality and pleasure in the analyzed films.